A comparative study between placental alpha microglobulin-1 rapid immunoassay and standard diagnostic methods for detection of rupture of membranes - Deshpande, Hemant; Sabale, Umesh; Madkar, C. S.; Bobe, Anuja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: To determine the efficacy of an immunoassay to measure levels of placental alpha-microglobulin-1 in cervico-vaginal secretions. Methods: 100 ANC cases admitted in Dr D. Y. Patil Hospital with symptoms of rupture of membranes during study period. Inclusion criteria-Pregnant women who presented with symptoms of ROM either in labour or not in labour, gestational age from 28 weeks onwards and who have given consent. Results: In 9 cases, the immunoassay test was negative, in 91 cases, it was positive and in one case, the liquor had a lot of meconium, the woman had to undergo an emergency cesarean section. This patient was deemed to have a false negative result by the test. Pooling was positive in 87 cases, nitrazine test in 86 cases and ferning in 88 cases. Hence, in comparison to immunoassay test which had 100% specificity and 98.91% sensitivity due to incomplete evaluation, nitrazine test had 95.58% sensitivity and 100% specificity, Pooling has 97.79% sensitivity and 100% specificity, whereas ferning has 98.34% sensitivity and 100% specificity. Conclusions: The PAMG1 is a non-invasive, rapid, one step test with very high sensitivity, specificity and accuracy as compared to the conventional methods together and also individually. Preforming this test instead of conventional methods can aid the early detection of rupture of membranes and largely affect the outcome of maternal and fetal health as timely decision can be taken once diagnosis is confirmed.